Latent Gene Sequencing Reveals Familial Relationships among Chinese Epstein-Barr Virus Strains and Evidence for Positive Selection of A11 Epitope Changes - Midgley, R. S. (American Society for Microbiology, 2003)
Epstein-Barr virus (EBV) strains from the highly HLA-A11-positive Chinese population are predominantly type 1 and show a variety of sequence changes (relative to the contemporary Caucasian prototype strain B95.8) in the nuclear antigen EBNA3B sequences encoding two immunodominant HLA-A11 epitopes, here called IVT and AVF. This has been interpreted by some as evidence of immune selection and by others as random genetic drift. To study epitope variation in a broader genomic context, we sequenced the whole of EBNA3B and parts of the EBNA2, 3A, and 3C genes from each of 31 Chinese EBV isolates. At each locus, type 1 viruses showed <2% nucleotide divergence from the B95.8 prototype while type 2 sequences remained even closer to the contemporary African prototype Ag876. However, type 1 isolates could clearly be divided into families based on linked patterns of sequence divergence from B95.8 across all four EBNA loci. Different patterns of IVT and AVF variation were associated with the different type 1 families, and there was additional epitope diversity within families. When the EBNA3 gene sequences of type 1 Chinese strains were subject to computer-based analysis, particular codons within the A11-epitope-coding region were among the few identified as being under positive or diversifying selection pressure. From these results, and the observation that mutant epitopes are consistently nonimmunogenic in vivo, we conclude that the immune selection hypothesis remains viable and worthy of further investigation.